PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN QUANTUM TEACHING DI KELAS IV SDN 03 ROROTAN - Pratiwi, Manda Giani; M. Kurnianti, Endang; Hasanah, Uswatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve students' critical thinking skills through the implementation of the Quantum Teaching learning model. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which was conducted in three cycles. The results showed that the implementation of the Quantum Teaching learning model improved students' critical thinking skills. The percentage of learning mastery increased from 31% in Cycle I, with a mean score of 61,38, to 48% in Cycle II, with a mean score of 72.05, and reached 96% in Cycle III, with a mean score of 86,96. Teacher activity improved from 77% in Cycle I to 92.50% in Cycle II and 96.50% in Cycle III, while student activity increased from 61% to 80.50% and 94%, respectively. Therefore, the Quantum Teaching learning model was proven to be effective in improving students' critical thinking skills in mathematics learning.